2010
DOI: 10.1159/000317519
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Aerobic Glycolysis by Inhibitors of Lactic Dehydrogenase Hinders the Growth of Human Hepatocellular Carcinoma Cell Lines

Abstract: Background/Aims:By reducing the number of ATP molecules produced via aerobic glycolysis, the inhibition of lactic dehydrogenase (LDH) should hinder the growth of neoplastic cells without damaging the normal cells which do not rely on this metabolic pathway for their energetic needs. Here, we studied the effect of oxamic and tartronic acids, 2 inhibitors of LDH, on aerobic glycolysis and cell replication of HepG2 and PLC/PRF/5 cells, 2 lines from human hepatocellular carcinomas. Methods:Aerobic glycolysis was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 36 publications
2
33
0
1
Order By: Relevance
“…When exposed to 40 mM (IC 50 value) of oxamate for 4 h, the production of lactic acid was reduced by 50%. The effective concentration of oxamate to suppress lactic acid production was similar to that previously reported (18,19). Hence, oxamate inhibits glycolysis in SGC-7901 cells.…”
Section: Morphological Changes In Gc Cells Treated With Oxamatesupporting
confidence: 87%
“…When exposed to 40 mM (IC 50 value) of oxamate for 4 h, the production of lactic acid was reduced by 50%. The effective concentration of oxamate to suppress lactic acid production was similar to that previously reported (18,19). Hence, oxamate inhibits glycolysis in SGC-7901 cells.…”
Section: Morphological Changes In Gc Cells Treated With Oxamatesupporting
confidence: 87%
“…Reprogramming of metabolism is a hallmark of the oncogene-induced transformation. 20,[38][39][40][41] In tumors this oncogene-reprogramming can also influence the metabolism of the host microenvironment. 42 Warburg's pioneering studies have discovered in the glycolytic phenotype under aerobic conditions a dominant marker of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, radiation resistance always results in subsequent recurrence and metastasis of cancer, which leads to treatment failure. It has been reported that inhibition of LDH sensitizes cancer cells to chemotherapy (18)(19)(20). However, the relationship between LDH inhibition and radiosensitivity is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A P-value <0.05 was considered to indicate a statistically significant result. confirm the LDH inhibition effect of oxamate as previously reported (18,19), a commercially available kit was used to determine the intracellular LDH enzyme activity after treatment with different doses of oxamate. The results showed that oxamate significantly decreased LDH activity (Fig.…”
Section: Assay Of Reactive Oxygen Species (Ros)mentioning
confidence: 97%
See 1 more Smart Citation